Agronomic, morphological and nutritional characteristics of Tithonia diversifolia in two environments with potential for use as forage (Bioagro, 2025)
Tithonia diversifolia is a shrub species that has gained increasing importance as an alternative species for forage due to its nutritional profile. Its agronomic and nutritional characteristics can vary depending on the environment. Therefore, the objective of this study was to evaluate the agronomic, morphological and nutritional characteristics of Tithonia diversifolia in two altitudinal zones of the Amazonas region, Peru. Plants were cultivated in Chachapoyas (2445 m.a.s.l.) and Cajaruro (797 m.a.s.l.), two locations with contrasting soil, climate, and altitude conditions. The bud burst, agronomic, morphological and nutritional characteristics of T. diversifolia were evaluated. The bud burst, dry weight, dry matter content, plant height, growth rate, carbohydrate content, and gross energy were significantly higher (p
Keywords: Altitude levels; germination; growth rate; nutrient; plant height